Molecular dynamics simulation of nanosized water droplet spreading in an electric field - Song, F H; Li, B Q; Liu, C (Langmuir, 2013)
Molecular dynamics (MD) simulations are performed for the spreading of a nanosized water droplet on a solid substrate subject to a parallel electric field. A combined electrostatic and Lennard-Jones potential is employed to represent the intermolecular interactions. Results show that in response to the applied field, polar water molecules realign themselves and this microscopic reorientation of molecular dipoles combines with the intermolecular forces to produce a macroscopic deformation of a free spherical water droplet into an ellipsoid. The applied field has a strong effect on the spreading of the water droplet on a solid substrate. For a weaker parallel field, the droplet spreading is asymmetric with the leading contact angle being greater than the trailing contact angle. With an increase in field strength, this asymmetry continues to increase, culminates, and then decreases until it disappears. The symmetric spreading remains with a further increase in the field strength until the saturation point is reached. This transition from the asymmetric to symmetric spreading is a manifestation of the interaction of the electric field with polar water molecules and the intermolecular forces within the droplet and between the water and solid; the interaction also leads to a change in hydrogen bonds along the droplet surface. The dynamics of the droplet spreading is entailed by the electrically induced motion of molecules along the liquid surface toward the solid substrate and is controlled by a competing mechanism among the electric, water-water, and water-solid intermolecular forces.